Challenges and coping strategies for providing maternal health care services among health care professionals in rural health facilities in Wolaita Zone, Southern Ethiopia: a qualitative study - Netsanet Demissie Milku; Diriba Wakjira Abose; Kelemu Abebe Gelaw; Taklu Marama Mokonnon; Makeda Sinaga Teshome (BMC, 2024)
Abstract Background Many factors can decrease job productivity and cause physical and psychological complications for health care professionals providing maternal care. Information on challenges and coping strategies among healthcare professionals providing maternal healthcare services in rural communities is crucial. However, there needs to be more studies, especially qualitative research, to explore challenges and coping strategies for providing maternal health care services in Ethiopia among health care professionals, particularly in the Wolaita zone. Objective To explore the challenges and coping strategies of professionals providing maternal health care in rural health facilities in Wolaita Zone, Southern Ethiopia, in 2023. Method A phenomenological qualitative study design was applied from May 20 to June 20, 2023. The study was conducted in rural areas of the Wolaita Zone, southern Ethiopia. Healthcare professionals from rural areas were selected using purposive sampling, and in-depth interviews were conducted. A qualitative thematic analysis was employed to analyze the data. Field notes were read, recordings were listened to, and each participant's interview was written word for word and analyzed using ATLAS.ti 7 software. Result Five main themes emerged from the data analysis. These themes included inadequate funding from the government, societal barriers to health and access to health care, professionals' personal life struggles, infrastructure related challenges and health system responsiveness, and coping strategies. Reporting to responsible bodies, teaching mothers about maternal health care services, and helping poor mothers from their pockets were listed among their coping strategies. Conclusion Healthcare professionals have a crucial role in supporting women in delivering babies safely. This study revealed that they are working under challenging conditions. So, if women's lives matter, then this situation requires a call to action.